Dinamika Kewenangan antara Lembaga Negara dan Otorita Ibu Kota Nusantara: Analisis Yuridis UU Nomor 21 Tahun 2023 - Ahmad Yusuf; Agus Riewanto; Andina Elok Puri Maharani (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2026)
The relocation of the capital from Jakarta to the Nusantara is a strategic policy with fundamental implications for Indonesia's constitutional architecture. Law No. 3 of 2022, as amended by Law No. 21 of 2023, established the IKN Authority, a sui generis ministerial-level institution granted special regional government authority and placed directly under the President. This hybrid position combines the functions of the central and regional governments, creating conceptual and practical challenges related to the distribution of authority, public accountability, and checks and balances. This study aims to analyze the existing mechanisms of relations between state institutions and the IKN Authority and formulate an ideal concept for realizing constitutional governance. Using normative legal research methods with legislative, conceptual, and comparative approaches, the study examines patterns of institutional relations within the framework of the theory of separation of powers and institutional relations. The results of this study indicate that the current legal design and practice of institutional relations tend to emphasize strategic centralization, which has the potential to create ambiguity of authority and deficits in legislative oversight mechanisms and fiscal accountability. Therefore, it is recommended to strengthen checks and balances through clarification of authority boundaries, increased fiscal and administrative accountability, and harmonization of inter-institutional norms to ensure the implementation of the IKN is accountable, transparent, and in accordance with the principles of the rule of law.